Rapid bioactivity-based pre-screening method for the detection of peptaibiotic-producing Trichoderma strains - Marik, Tamás (Acta Biologica Szegediensis, 2013)
Peptaibiotics are bioactive secondary metabolites belonging to a constantly growing family of fungal peptide antibiotics. They are linear, amphipathic oligopeptides consisting of 5-20 amino acids, usually containing nonproteinogenic amino acid residues as characteristic building blocks of the structure. The majority of the peptaibiotics described so far are produced by members of the filamentous fungal genus Trichoderma. Species of this genus are known as important sources of antibiotics and enzymes, and they are also known as promoters of plant growth, decomposers of xenobiotics and as commercial biofungicides. In this work, a rapid, bacterium-based screening method was developed and optimized for the detection of peptaibiotic production in liquid cultures of Trichoderma strains. The method was validated with the commercially available alamethicin as a peptaibiotic reference compound.